Preparation condition optimization and stability of cubic phase CdS in photocatalytic hydrogen production. (29th March 2021) - Li, Yixian; Yin, Mingcai; Sun, Jiangfan; Liang, Kaiyue; Fan, Yaoting; Li, Zhongjun
Abstract : Cubic CdS prepared with a Cd : S ratio of 5 : 8 and an aging time of 6 h exhibits excellent activity and phase stability. Abstract : Cadmium sulphide (CdS) is a promising material for photocatalytic hydrogen production. Compared with hexagonal CdS (h-CdS), the research on cubic CdS (c-CdS) is much less. Especially, detailed studies on the preparation condition optimization and photostability of c-CdS are still insufficient. In this paper, c-CdS was prepared by a simple precipitation method and characterized by XRD, SEM, TEM and XPS techniques. Firstly, the Cd to S molar ratio and aging time were optimized to find out their influences on the crystal structure, morphology, chemical state and hydrogen production performance of CdS. The c-CdS obtained at a Cd : S ratio of 5 : 8 and an aging time of 6 h (denoted as CdS-8-6) possesses the highest performance of 37.7 μmol h −1 . Secondly and more importantly, cyclic hydrogen production tests were conducted on CdS-8-6 and a series of determinations were carried out on the recovered samples to investigate its photostability during reaction.